Effect of Current Ratio, Return on Equity, Managerial Ownership, Sales Growth, and Asset Structure on Capital Structure in Retail Trade Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Siti Dini; Vanessa Vanessa; Juvina Juvina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this test and analysis is to determine effect of current ratio, return on equity, managerial ownership, sales growth, and asset structure on capital structure in Retail Trade Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method used is a quantitative approach. This population chose the Retail Trade Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. In order to obtain the sample to be studied, purposive sampling technique was used. The total number of samples obtained were 7 issuers of the Retail Trade Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research strategy uses multiple linear regression technique. Multiple linear regression technique consists of partial test (t), simultaneous test (F), and coefficient of determination test (R2). The results of partial test (t) show that current ratio and return on equity have a significant effect on capital structure. Meanwhile, managerial ownership, sales growth, asset structure have no a significant effect on capital structure. Simultaneous test results (F) show that current ratio, return on equity, managerial ownership, sales growth, and asset structure have a significant effect on capital structure. The results of the coefficient of determination test (R2) show that adjusted r square value of 0.820 means that capital structure is explained through the independent variables of 82 percent and the remaining 18 percent of capital structure is explained from other variables that are not included in this regression.